Algumas propriedades de semigrupos de dimensão de imersão 3 - Orduña, Miguel Angel Aguilar (2025)
In this work, we conduct an in-depth study of numerical semigroups, exploring both their fundamental properties and other important concepts. We extensively rely on basic theory to derive less intuitive and more complex results. We focus our research on a specific class of numerical semigroups: those with embedding dimension equal to 3. To this end, we examine relevant aspects of the theory, including free monoids, presentations of numerical semigroups, gluing of numerical semigroups, and free numerical semigroups, among other essential topics. Furthermore, we dedicate ourselves to the study of perfect numerical semigroups, analyzing some of their properties and their interactions with other properties.